One-pot green synthesis of anisotropic silver nanoparticles. Issue 6 (17th October 2016) - Hosseinidoust, Zeinab; Basnet, Mohan; van de Ven, Theo G. M.; Tufenkji, Nathalie
Abstract : Anisotropic silver nanoplates are of interest for their shape-dependent properties; however, their synthesis often requires surfactants and toxic chemicals. Abstract : Anisotropic silver nanoplates are of interest for their shape-dependent properties; however, their synthesis often requires surfactants and toxic chemicals. We report the first one-pot method for the green synthesis of colloidally stable triangular, hexagonal and dendric silver nanostructures, enabled by the unique physical and chemical architecture of "hairy" cellulose nanocrystals (CNCs). Silver nanoplates were formed by irradiating a suspension of CNCs and silver nitrate in a UV chamber for as little as 5 min. Electron microscopy and diffraction analysis revealed that CNCs with low carboxyl content resulted in single crystal thin triangular nanoprisms. Increasing the CNC carboxyl content resulted in hexagonal nanosheets and flower-like/dendric structures. The synthesized nanoplates exhibited shape-dependent catalytic performance for methylene blue degradation.